Calcul des structures et architectures de logiciels - Debordes, Olivier (European Journal of Computational Mechanics, 2000)
For the past thirty years, the evolution of structural analysis softwares has been closely related to the evolution of computer science. Hence, we study how the recent developments of object concepts may influence the architecture of softwares for numerical modeling and simulation, for software editors as well as for research laboratories or groups in the field of finite element methods. We point out the concepts of data structures, of methods associated to objects and of relations between objects, as well as the concept of modeling language as a way to enhance significantly such softwares.